New collagen‐coated calcium phosphate synthetic bone filler (Synergoss®): A comparative surface analysis. Issue 4 (17th January 2018) - Iviglia, Giorgio; Morra, Marco; Cassinelli, Clara; Torre, Elisa; Rodriguez Y Baena, Ruggero
Abstract: Replacement of bone loss or reconstruction of bone defect is still a clinical challenge. Synergoss ® is a recently developed synthetic bone filler that exploits biomolecular surface engineering to deliver directly to the filler‐implant interface the signaling properties of type I collagen. In this article, we compared Synergoss ® bone filler with the most used materials present on the market derived from animal source (Bio‐Oss ®, Gen‐Os ® ) or synthetic source (BoneCeramic ® ). All tested bone fillers were analyzed by ATR‐IR, providing information concerning the chemical composition and the main functional groups. Surface zeta potential analysis shows a positive surface charge for Synergoss ®, confirming that the material exposes a collagen nanolayer to the surrounding environment, unlike typical synthetic and bone‐based fillers. The chemical composition of the first few nanometers of the surface of tested bone fillers was evaluated by XPS, and Synergoss ® shows a significant amount of nitrogen (9.8 at%), which is not detected in any of the remaining materials. Morphological structure of Synergoss ® (analyzed by SEM) shows a uniformly distributed micro‐ and macroporosity, which plays an essential role in influencing cell adhesion and blood vessel infiltration, nutrient transportation, and clot formation to stimulate the overall healing process.